Gender awareness in student teachers at the University of Turku - Casteleyn, Maxime (My University, 2022)
The aim of the study was to map gender awareness in student teachers in the teacher education program at the University of Turku. In 2014 the new Finnish national core curriculum added the inclusion of knowledge and understanding of gender diversity to the basic education curriculum, furthermore, according to renewed legislation, a plan to include gender equality must be in place in all educational institutions. Therefore, this study focused on the perceived knowledge and understanding of gender sensitivity, gender stereotypes and biases of students teachers, as well as what has been taught in their teacher education on gender awareness. For the mapping of gender awareness, the development of a new questionnaire was needed, in combination with semi-structured interviews with participants to explore the aforementioned topics on a deeper level. The findings of this study revealed strong subscales in the questionnaire that measured gender stereotypes towards students and teachers, gender sensitivity in the classroom and gender awareness in teacher education. The participants in this study revealed to not possess too much of a stereotypical thinking except in regards to the behaviour of boys and reported the belief of male student teachers being more appreciated in the teaching profession. Furthermore, participants presented an intention to act in a gender sensitive manner in the classroom though they reported a lack of education on gender issues that should be offered in the teacher education program. Within the teacher education program, if gender was addressed in courses, this was often done in heteronormative and gender stereotypical ways. Lastly, teachings on transgender and gender non-conforming issues were reported to be non-existent in the program. As a result, recommendations towards the education on gender issues are provided, as well as further research into the perceptions of teachers towards different genders. In general, the complexity of research into gender awareness should not be underestimated and was corroborated by the findings of the underlying patterns in answers to the survey.
Keywords: gender awareness, gender in education, teacher education, interview, survey, gender sensitivity, gender non-conforming, heteronormativity